Neuroprotective effects of melatonin and celecoxib against ethanol-induced neurodegeneration: a computational and pharmacological approach - Al Kury LT; Zeb A; Abidin ZU; Irshad N; Malik I; Alvi AM; Khalil AAK; Ahmad S; Faheem M; Khan AU; Shah FA; Li S (Dove Medical Press, 2019)
Lina T Al Kury,1 Alam Zeb,2 Zain Ul Abidin,2 Nadeem Irshad,3 Imran Malik,2 Arooj Mohsin Alvi,2 Atif Ali Khan Khalil,4 Sareer Ahmad,4 Muhammad Faheem,2 Arif-Ullah Khan,2 Fawad Ali Shah,2 Shupeng Li51College of Natural and Health Sciences, Zayed University, Abu Dhabi, United Arab Emirates; 2Riphah Institute of Pharmaceutical Sciences, Riphah International University, Islamabad, Pakistan; 3Department of Pharmacy, Quaid-I-Azam University, Islamabad, Pakistan; 4Rehman Medical Institute, Peshawar, Pakistan; 5State Key Laboratory of Oncogenomics, School of Chemical Biology and Biotechnology, Peking University Shenzhen Graduate School, Shenzhen 518055, People’s Republic of ChinaPurpose: Melatonin and celecoxib are antioxidants and anti-inflammatory agents that exert protective effects in different experimental models. In this study, the neuroprotective effects of melatonin and celecoxib were demonstrated against ethanol-induced neuronal injury by in silico, morphological, and biochemical approaches.Methods: For the in silico study, 3-D structures were constructed and docking analysis performed. For in vivo studies, rats were treated with ethanol, melatonin, and celecoxib. Brain samples were collected for biochemical and morphological analysis.Results: Homology modeling was performed to build 3-D structures for IL1β), TNFα, TLR4, and inducible nitric oxide synthase. Structural refinement was achieved via molecular dynamic simulation and processed for docking and postdocking analysis. Further in vivo experiments showed that ethanol induced marked neuronal injury characterized by downregulated glutathione, glutathione S-transferase, and upregulated inducible nitric oxide synthase. Additionally, ethanol increased the expression of TNFα and IL1β. Finally, neuronal apoptosis was demonstrated in ethanol-intoxicated animals using caspase 3 and activated JNK staining. On the other hand, melatonin and celecoxib treatment ameliorated the biochemical and immunohistochemical alterations induced by ethanol.Conclusion: These results demonstrated that ethanol induced neurodegeneration by activating inflammatory and apoptotic proteins in rat brain, while melatonin and celecoxib may protect rat brain by downregulating inflammatory and apoptotic markers.Keywords: simulation, docking, cortex, hippocampus, ethanol, neurodegeneration